Comparison of high definition with standard white light endoscopy for detection of dysplastic lesions during surveillance colonoscopy in patients with inflammatory bowel disease. (13th March 2011) - Subramanian, V; Telakis, E; Ramappa, V; Mannath, J; Jawhari, A; Ragunath, K; Hawkey, C J
Abstract : Introduction: Dysplasia in colonic inflammatory bowel disease (IBD) is often multifocal and flat, making it easy for significant lesions to be overlooked. Dye spraying the mucosal surface is believed to enhance visualisation of subtle mucosal abnormalities, but is cumbersome and messy and has poor uptake among endoscopists. High definition (HD) colonoscopy improves adenoma detection rates by improving the ability to detect subtle mucosal changes and is as good as chromoendoscopy in polyp detection. The utility of high definition colonoscopy in dysplasia detection in patients with IBD has not been reported so far. The authors aimed to compare the yield of dysplastic lesions detected by standard definition white light endoscopy (SD) with high definition endoscopy (HD). Methods: Details of consecutive patients with long standing (>7 years) colonic IBD who underwent surveillance colonoscopy at Nottingham University Hospitals between September 2008 and February 2010 were extracted from the endoscopy database. Details of diagnosis, duration of disease and outcomes of the colonoscopy were then collected from the electronic patient records and patient notes. The colonoscopies were done at 2 sites, of which one had only HD systems and the other SD. SPSS v17 was used for the data analysis. Results: 360 colonoscopies were done on 353 patients. There were 162 colonoscopies (102 UC and 60 CD) in the SD group and 208 colonoscopies (146 UC and 62 CD), in the HD group. The groups were well matched for mean age of patients, duration of disease, gender and number of biopsies taken. Table 1 gives information on the number and characterisation of dysplastic lesions detected. Conclusion: HD colonoscopy is superior to SD colonoscopy in targeted detection of dysplastic lesions during surveillance colonoscopy of patients with colonic IBD in routine clinical practice. HD colonoscopy could facilitate endoscopic resection in these patients. Randomised controlled studies are required to confirm these findings.